THE UTILIZATION OF LOCAL POTENTIAL TO MAKE HEALTHY FOOD IN CHILDREN FROM KNOWLEDGE AND SKILL IMPROVEMENT IN VILLAGE BENDA BARU, KECAMATAN PAMULANG-TANGERANG SELATAN - Hendrawan, Rina Febriana; Nur Riska; Rusilanti (LPPM Universitas Negeri Jakarta, 2022)
The implementation of the P2M program is community empowerment in the Benda Baru village, Pamulang District, South Tangerang in the form of utilizing local potential to make healthy food for toddlers to increase knowledge and skills in the town of new objects. The methods used in this activity were the provision of material, direct practice, and mentoring. Pelican was attended by 20 participants namely 15 mothers and five children under five and carried out on Saturday 15 September 2018. The results of pretest data had obtained at a range of 60 values. -80 with enough categories as much as 27%. While the post-test data at the cost of> 80 with a suitable type of 67%. Based on the results of calculations with an average of 8.87, it indicates that the participants have received the material delivered by the instructor. The increase in pre-test and post-test on maternal knowledge was only a difference of 1.81. This increase is expected to contribute to the experience that is useful in processing and serving healthy food for children.